Analisis Damage Cargo Menggunakan Failure Mode And Effect Analysis (Fmea) Pada Terminal Kargo Domestik Bandara I Gusti Ngurah Rai (Studi Kasus Perusahaan Jasa Kargo PT. I) - Efendi, Badriya Ivo; Dewi, Dinar Kania; Poncotoyo, Wahyu (Jurnal Sistem Transportasi & Logistik, 2023)
PT. I is one of the logistics sector companys that provides several services including Cargo Terminal. Based on the data obtained through observation and document archives, it was found that some cargo damage was wet, leaking, torn, etc.. Using a qualitative approach where the methode used is Fault Tree Analysis (FTA), Failure Mode and Effect Analysis (FMEA) and quantitative approach to find the RPN value through a questionnaire. It was found that wet cargo was the most damaged, followed by torn and breakage cargo. The factors caused damage is lack of preparation for handling during rainy wheather, incorrect use of packaging, and handling loading and unloading of goods that are not in accordance with the standart operational procedure. And effects caused by the contents of the cargo being wet, the packaging is rotten, torn, and opened also the cargo is broken, dent, and leaking. Damage to cargo is a major problem in logistics, because its the priority and is considered the most important is the integrity and condition of the goods sent. If this is allowed, it will result in the value of the quality logistics company by its customers.